The Relationship Between The Two Listening And Speaking Abilities In The Acquisition Of Students Speaking Skill At MAN/PK 2 Padang Panjang - Monica Syahara; Oktarina Yusra; Fajriyani Arsya; Nur Hasnah (Universitas Pahlawan Tuanku Tambusai, 2023)
thesis was prepared by Monica Syahara, registration number: 2218071. Departement Arabic language education, college of education and educational sciences, Syeikh Muhammad Djamil Djambek State Islamic University, Bukittinggi, with the topic: “ The relationship between the skills of listening and speaking in the achievement of speaking skill among students at the High School of the Religious Padang Panjang” The problems in this research mean that male and female students do not have a good ability to hear Arabic speech in the form of dialogues and conversations that male and female students listened to through a device, a recorder or from the teacher himself.In this research, the author uses the relational research approach, the method presented by the symbol “korelasi Product Moment”, and the author follows the hypothetical test. The purpose of two exms is to take the extract correctly and also to know the quality of the writer, so the writer uses the interpretation of the results “r” Thus, the author presents the accompanying writing to this high relationship, which is positive. As for my result, which is 0,037, the high relationship and the extent of integration between the skills of listening and speaking in the linguistic achievement of students on the keen ear by nature to deliver language to the hearing and understanding centers in the brain.